1818 Terr. of Mo. Laws 374 - (:unkn) unknown (My University, 1818)
Prohibited "slave or mulatto" from carrying a gun, powder, shot, club or other weapon and from possessing a gun or ammunition.
Keywords: ENSLAVED PERSONS & OTHER MINORITIES